KNOWLEDGE REGARDING PREVENTION OF MOSQUITO BORNE DISEASES AMONG ADULTS IN NARATH PANCHAYAT, KANNUR DISTRICT - NEETHU MARIA BABU (JOURNAL OF INTERNATIONAL ACADEMIC RESEARCH FOR MULTIDISCIPLINARY, 2014)
The objective of the study is to assess the knowledge regarding prevention of mosquito borne diseases among the adults residing in Narath panchayat, to find the association between the knowledge score and selected demographic variables like age, gender, education and occupation. Descriptive survey design with convenient sampling technique to collect data from 150 samples residing in Narath panchayat, Kannur District. Major findings of the study showed that most of the people (27.33%) belonged to the age group of 18-28 years and were females (80.67%).20.67% of the sample had higher secondary level of education and 57.33% were unemployed. The scores from the knowledge questionnaire revealed that only 15.3% of the people had adequate knowledge, 76.6% of people had moderately adequate knowledge and 8% had inadequate knowledge regarding prevention of mosquito borne diseases. The other findings of the study revealed that there was no significant association between knowledge scores and selected demographic variables like age, gender, education and occupation. The study concluded that the knowledge in the respective field is inadequate among the adults and so it is important to initiate actions to enhance the knowledge of the people in the community so that they can take necessary measures to prevent diseases.